Study of Previous Concrete Using Silica Fume (International Journal of Innovative Research in Engineering & Management, 2023)
A concrete type with a significant porosity  is pervious concrete. It is applied to concrete flat  constructions so that water can travel through it.. A  commercial by-product created during the manufacturing of  silicon metal or silicon alloys is silica fume. It is also  known that silica fume enhances the mechanical properties  of concrete. The main physical impact of silica fume in  concrete is that it acts as a filler. Sand fills the spaces  between the particles of coarse aggregate, and cement  grains fill the spaces between sand grains because of their  similar sizes. This highly active pozzolan reacts more  quickly than regular pozzolans in terms of the chemical  reaction of silica fume due to its high surface area and high  amount of amorphous silica. The use of silica fume in  concrete offers both engineering and financial benefits. This  study discusses the ideal silica fume content for the cost effective and sustainable manufacture of concrete based on  the findings of experimental research. When used as a  partial replacement for opc, silica fume is shown to work  best at a level of 15% (by weight). Utilizing silica fume  raises strength metrics significantly while reducing  workability.
Keywords: Silica Fume; Opc; Compressive Strength; Flexural Strength